Measuring Leaf Water Potential - Christian Bartell; Haimanote K. Bayabil; Bruce Schaffer; Fitsum Tilahun; Fikadu Getachew (EDIS)
This article summarizes the basic concepts of leaf water potential measurements and two available methods for measuring leaf water potential under field and laboratory conditions. Written by Christian Bartell, Haimanote K. Bayabil, Bruce Schaffer, Fitsum Tilahun, and Fikadu Getachew, and published by the UF/IFAS Department of Agricultural and Biological Engineering, October 2021.